Transformasi Kreativitas Kidung Jerum Dalam Novel Jerum Sebagai Sastra Kontemporer - Juliana, I Wayan (Jayapangus Press, 2025)
Kidung Jerum as part of Balinese literature has developed widely with its function as a medium for ceremonies, especially bhuta yadnya. In the midst of its popularity, the story of Kidung Jerum is not widely known by the general public because in the process of singing it only a few verses are taken. As an effort to popularize the story of Kidung Jerum to a wider area, a media conversion was carried out. The process of converting Kidung Jerum into the Jerum novel is a creative process that can expand the scope of reading traditional literary works. In the form of a novel, the story of Ni Jerum and Kundangdia has a wider target audience both locally and nationally. This change in form is something interesting that is important to study in a study, whether the Jerum novel immediately imitates Kidung Jerum, is there a creative process in the form of character and story expansion, is the ideology in the kidung also inherited into the novel? Of course, all these questions will be answered in the discussion of this study. The purpose of this study is to reveal the extent to which the Jerum novel is dependent on adapting the story of Kidung Jerum. In this study, the theory used is intertextual theory. The method used to support this research is the comparative method. This method is done by carefully reading both works and comparing them to see how the transfer of ideology from kidung into the novel. The results of this study show the sustainability of the construction of the network structure that forms kidung Jerum in the novel Jerum, secondly, the transformation of the main motifs of kidung Jerum (hypogram) into the novel Jerum (apogram) in the form of the motif of the command to marry, the motif of the emergence and acceptance of love, the motif of post-death, the motif of revenge, the motif of life again.